Noise exposure-induced the cerebral alterations: From emerging evidence to antioxidant-mediated prevention and treatment - Yuyan Chen; Jie Huang; Zhiying Zhou; Jiaping Zhang; Chaohui Jin; Xiansi Zeng; Jinjing Jia; Li Li (Ecotoxicology and Environmental Safety)
It’s well acknowledged that noise exposure has become a major environmental risk factor of public health. The previous standpoint holds that the main harm of noise exposure is to cause hearing loss of human. However, in the past two decades a large number of studies have linked the noise exposure to various cerebral changes. In this review, we summarized that noise exposure led to cerebral changes through breaking the redox balance, inducing neuroinflammation and neuronal apoptosis and altering the neurotransmission in numerous brain areas, including cortex, thalamus, hippocampus, amygdala, striatum and cerebellum. Those cerebral changes finally result in a variety of disorders, such as tinnitus, anxiety, depression, cognitive impairment and motor dysfunction. Furthermore, we reviewed several antioxidants, such as resveratrol, vitamin C, curcumin, N-acetylcysteine and α-asarone, and highlighted their protective mechanisms against noise exposure, aiming to provide a promising strategy to prevent and treat noise exposure-induced diseases. Taken together, noise exposure induces various cerebral changes and further leads to disorders in the central nervous system, which can be ameliorated by the treatment with antioxidants.